Fragmentation and the European patent system - Walsh, Karen, 1987- (Hart, 2022)
"This book examines current perceptions of, and responses to, fragmentation in the European patent system (EPS). For decades, attempts have been made to address this fragmentation by introducing a unitary patent system. Based on an analysis of the current and forthcoming system, the book argues that the inherent nature of fragmentation within the EPS needs to be recognised and suggests that a multifaceted approach is required to respond to it. It draws on work regarding fragmentation outside of the patent and intellectual property regimes, gaining insights from both European law-making and the international legal system. It investigates current responses to fragmentation in the EPS. Interpretations of substantive patent law are examined, including claim construction (Actavis v Eli Lily), exceptions to patentability related to uses of human embryos for industrial or commercial purposes (WARF, Brustle, ISCC), and products resulting from essentially biological processes (Broccoli and Tomatoes II, G3/19)"--Adapted from the publisher's description.